Comparative analysis of the plasma parameters of ECR and combined ECR + RF discharges in the TOMAS plasma facility. (12th November 2021) - Kovtun, Yu; Wauters, T; Goriaev, A; Möller, S; López-Rodríguez, D; Crombé, K; Brezinsek, S; Dinklage, A; Nicolai, D; Linsmeier, Ch; Van Schoor, M; Buermans, J; et al.
Abstract: The toroidal magnetized system (TOMAS) plasma facility aims at complementary research on wall conditioning methods, plasma production and plasma–surface interaction studies. This paper explores for the first time the parameters in helium electron-cyclotron resonance (ECR) plasma and combined ECR + radio-frequency (RF) discharges in TOMAS. The ECR discharge in this work, at 2.45 GHz and 87.6 mT, is the main one for creating and maintaining the plasma, while the addition of RF power at 25 MHz allows to broaden the achievable electron temperature and density at a given gas flow, as evidenced by triple Langmuir probe measurements. This effect of the combined ECR + RF discharge provides flexibility to study particular aspects of wall conditioning techniques relevant to larger devices, or to approach plasma conditions relevant to fusion edge plasmas for particular surface interaction studies.